Quantitative Assessment of Service Quality and Client Satisfaction in the Philippine Public Sector: A Case Study of a National Regulatory Agency - Libunao, Mark Anthony; Gaddi, Felix Joshua (Journal of Interdisciplinary Perspectives, 2025)
This study investigates the relationship between service quality and client satisfaction in the Philippine public sector, with a specific focus on the Games and Amusements Board (GAB). Despite the growing emphasis on citizen-centered governance, limited empirical studies have examined how service quality dimensions influence client satisfaction in regulatory agencies that supervise professional sports and games. Addressing this gap, the study aimed to assess the impact of the SERVQUAL dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy, on the satisfaction of clients using services from GAB. Utilizing a quantitative research design, data were collected from 408 respondents through a structured survey instrument. Descriptive statistics, Pearson correlation, and stepwise multiple linear regression analysis were employed to analyze the data. Results revealed that all five service quality dimensions have a statistically significant and positive correlation with client satisfaction. Among them, empathy (B = 0.325, p < 0.001) emerged as the strongest predictor, followed by responsiveness (B = 0.299, p < 0.001) and tangibility (B = 0.191, p < 0.001). The model yielded an R2 value of 0.815, indicating that the SERVQUAL dimensions can explain 81.5 percent of the variance in client satisfaction. These findings emphasize the critical importance of strengthening GAB’s service delivery, particularly in terms of understanding client needs, providing timely and helpful responses, and maintaining clean facilities, well-maintained equipment, and the professional appearance of staff. While tangibility may not connect with clients on an emotional level like empathy or respond to their needs as directly as responsiveness, it still helps shape how clients perceive the quality of service and whether they can trust it. The study provides empirical evidence to support quality enhancement initiatives and performance reforms in the public service sector. It concludes with recommendations for continuous service quality assessment and stakeholder engagement to sustain client-centered regulatory practices.